2022
DOI: 10.1099/ijsem.0.005411
|View full text |Cite
|
Sign up to set email alerts
|

Nonomuraea aurantiaca sp. nov., a novel cellulase-producing actinobacterium isolated from soil

Abstract: A novel cellulase-producing actinobacterium, designated strain NEAU-L178T, was isolated from soil sample collected from Qiqihaer, Heilongjiang Province, PR China. A polyphasic study was carried out to determine the taxonomic status of the strain. On the basis of 16S rRNA gene sequence analysis, strain NEAU-L178T should be classified into the genus Nonomuraea and is closely related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 50 publications
(64 reference statements)
1
0
0
Order By: Relevance
“…The cellular fatty acids of strain MCN248 T that comprised more than 10% of total fatty acids were iso-C16:0 (40.4%), 10-methyl- C17:0 (22.0%), and C17:1ω8c (10.9%) ( Table 1 ). The chemotaxonomic traits were consistent with those of other species in the genus ( Saygin et al, 2021 ; Lin et al, 2022 ), as reported in Bergey’s Manual of Systematics of Archaea and Bacteria ( Kämpfer, 2012 ). Madurose is the major sugar, and MK-9(H 4 ), MK-9(H 2 ), and MK-9(H 0 ) are mainly found as the menaquinones.…”
Section: Resultssupporting
confidence: 84%
“…The cellular fatty acids of strain MCN248 T that comprised more than 10% of total fatty acids were iso-C16:0 (40.4%), 10-methyl- C17:0 (22.0%), and C17:1ω8c (10.9%) ( Table 1 ). The chemotaxonomic traits were consistent with those of other species in the genus ( Saygin et al, 2021 ; Lin et al, 2022 ), as reported in Bergey’s Manual of Systematics of Archaea and Bacteria ( Kämpfer, 2012 ). Madurose is the major sugar, and MK-9(H 4 ), MK-9(H 2 ), and MK-9(H 0 ) are mainly found as the menaquinones.…”
Section: Resultssupporting
confidence: 84%